Effect of multiple passes and overlap rate parameters in waterjet cleaning for paint removal using RSM - Mat Nawi, Mohd Nazir; Husin, Hafiz; Gebremariam, Mebrahitom Asmelash; Saptaji, Kushendarsyah; Azhari, Azmir (Springer, 2025)
The utilization of waterjet technology has been expanded to encompass various applications such as surface treatment, cleaning, and material cutting. Particularly in the field of cleaning, waterjet is a commonly employed method due to its environmentally friendly nature thus leading to minimal pollution in the vicinity. The primary objective of the present work is to investigate the effect of cleaning parameters namely pressure, number of jet passes, jet overlap, and abrasive flow rate on surface roughness, material removal rate, and cleaning efficiency during waterjet cleaning of mild steel-painted surfaces. Response surface methodology (RSM) was adopted utilising analysis of variance (ANOVA), and fractional factorial design at two levels to examine the significance and interactions of cleaning parameters on studied responses. The investigation revealed that the abrasive flow rate and pressure proved to be the most influential factors in determining the efficacy of the paint cleaning process.